SIKAP PARENTING GURU PAUD; STUDI KOMPARATIF ANTARA GURU PAUD BERSERTIFIKASI DENGAN GURU PAUD BELUM BERSERTIFIKASI DI KALIMANTAN SELATAN - Ika Irayana; Murniati Ismail (Fakultas Tarbiyah IIQ Jakarta, 2024)
Parents require support from teachers in apprehending and executing positive parenting, necessitating teachers' comprehension and mastery of positive parenting. The teacher certification is a programme intended to enhance teacher competency, encompassing parenting proficiency. Thus, it is crucial to chart the aptitude in parenting of Early Childhood Education (ECE) teachers in South Kalimantan, while also ascertaining the contrast in efficacy between certified and uncertified teachers. This study employed a quantitative methodology with a comparative descriptive design. The total population under investigation was 10,204 individuals, and the sample size was determined through application of the Slovin formula, yielding 385 participants with a 95% significance level. A summary of parental attitudes among certified teachers revealed that 9.5% of participants rated low, 56.9% medium, and 34% high in their attitudes. In the group of teachers lacking certification, the distribution of parenting attitudes is 16.5% in the low category, 71.7% in the moderate category, and 11.4% in the high category. The Mann-Whitney test table output indicates an Asymp. Sig. (2-tailed) value of 0.000, which is below the probability threshold of 0.05. Hence, a notable contrast emerges in the approach of PAUD teachers towards parenting depending on whether they are certified or not.